2018
DOI: 10.24843/ejmunud.2018.v07.i10.p18
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Keputusan Investasi, Keputusan Pendanaan Dan Kebijakan Dividen Terhadap Nilai Perusahaan Food and Beverages

Abstract: Companies that want to maximize the value of the company, will take some decisions such as investment decisions, dividend policies, and funding decisions. The purpose of this study is to explain the effect of investment decisions, funding decisions, and dividend policy on the value of food and beverages companies listed on the Indonesia Stock Exchange. The samples used in this study were selected in saturation sampling. Secondary data obtained then selected based on predetermined criteria, then obtained as man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1
22

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 0 publications
2
6
1
22
Order By: Relevance
“…This result is in accordance with the signal theory which states that a company with a high DPR level will be a signal for investors and the company will gain high trust from investors. These results are consistent with research conducted by Utami & Darmayanti (2018) and Musabbihan & Purnawati (2018) which found that there is an effect of dividend policy on firm value…”
Section: Dividend Policy Has a Positive Effect On Firm Valuesupporting
confidence: 92%
“…This result is in accordance with the signal theory which states that a company with a high DPR level will be a signal for investors and the company will gain high trust from investors. These results are consistent with research conducted by Utami & Darmayanti (2018) and Musabbihan & Purnawati (2018) which found that there is an effect of dividend policy on firm value…”
Section: Dividend Policy Has a Positive Effect On Firm Valuesupporting
confidence: 92%
“…Kebijakan dividen adalah keputusan apakah laba yang diperoleh perusahaan akan dibagikan kepada pemegang saham sebagai dividen atau akan ditahan untuk menambah modal investasi di masa yang akan datang (Utami et al, 2018). Jika yang diputuskan yaitu membagikan dividen maka dapat mengurangi laba ditahan sehingga dapat mengurangi dana internal, namun apabila tidak membagikan dividen maka perusahaan dapat meningkatkan…”
Section: ) Kebijakan Dividenunclassified
“…Terkait dengan penelitian ini, sebelumnya telah diteliti oleh Utami dan Ni Putu Ayu (2018). Tetapi pada penelitian sebelumnya belum menggunakan variabel moderasi.…”
Section: Pendahuluanunclassified